Contribution To Empowerment Of Tourism Industry To Community Welfare - Azidni Rofiqo; Abdul Hamid; Tri Wijayanti Septiarini (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to examine the effect of empowerment on welfare. Empowerment here is proxied by empowering, fostering, supporting, and protecting. Welfare is meant as a maqoshid sharia as measured by hifdz addin, an nafs, al nasl, al aql, and al mal. This study proposes a hypothesis of empowering, fostering, supporting, and protecting a positive effect on welfare. This research was conducted in 2019-2020 which took place at Ngebel Lake with 50 respondents in the tourism sector. This type of research is quantitative with questionnaire data collection that can be measured by a Likert scale. Data analysis through classical assumption test and multiple linear regression. The results of the analysis show that empowering, supporting, and protection have a significant positive effect on welfare. Fostering has no significant effect on welfare. Adjusted R-square value, 0.798119 which states that the four independent variables contributed 79% to the dependent variable. This research is limited to the place, time and samples. Future research is expected to be more comprehensive.